The global South Atlantic - Bystrom, Kerry, 1977-; Slaughter, Joseph R. (Fordham University Press, 2018)
Countering a Northern focus in much Atlantic World scholarship, this volume brings together new scholarship in comparative literary studies, cultural studies and history which explores the South Atlantic as a region, or the way the Atlantic more widely has been viewed from the Global South.